Effects of Deltamethrin Acute Exposure on Nav1.6 Channels and Medium Spiny Neurons of the Nucleus Accumbens. (July 2020) - Tapia, Cynthia M.; Folorunso, Oluwarotimi; Singh, Aditya K.; McDonough, Kathleen; Laezza, Fernanda
Graphical abstract: Abstract: Exposure to pyrethroids, a popular insecticide class that targets voltage-gated Na+ (Nav) channels, has been correlated to an increase in diagnosis of neurodevelopmental disorders, such as attention deficit hyperactive disorder (ADHD), in children. Dysregulation of medium spiny neurons (MSNs) firing in the nucleus accumbens (NAc) is thought to play a critical role in the pathophysiology of ADHD and other neurodevelopmental disorders. The Nav1.6 channel is the primary molecular determinant of MSN firing and is sensitive to modification by pyrethroids. Building on previous studies demonstrating that deltamethrin (DM), a commonly used pyrethroid, leads to use-dependent enhancement of sodium currents, we characterized the effect of the toxin on long-term inactivation (LTI) of the Nav1.6 channel, a parameter known to affect neuronal firing, and characterized changes in MSN intrinsic excitability. We employed whole-cell patch-clamp electrophysiology to measure sodium currents in HEK-293 cells stably expressing Nav1.6 channels and intrinsic excitability of MSNs in the brain slice preparation. We found that in response to repetitive stimulation acute exposure to 10 μM DM potentiated a build-up of residual sodium currents and modified availability of Nav1.6 by inducing LTI. In the NAc, DM modified MSN intrinsic excitability increasing evoked action potential firing frequency and inducing aberrant action potentials with low amplitude and depolarized voltage threshold, phenotypes that could be explained by DM induced changes on the Nav1.6 channel. These results provide a potential initial mechanism of toxicity of DM that could lead to disruption of the NAc circuitry overtime, increasing the risk of ADHD and other neurodevelopmental disorders.